Zeolitic imidazolate framework-coated acoustic sensors for room temperature detection of carbon dioxide and methane. Issue 17 (19th April 2018) - Devkota, Jagannath; Kim, Ki-Joong; Ohodnicki, Paul R.; Culp, Jeffrey T.; Greve, David W.; Lekse, Jonathan W.
Abstract : The integration of nanoporous materials such as metal organic frameworks (MOFs) with sensitive transducers can result in robust sensing platforms for monitoring gases and chemical vapors for a range of applications. Abstract : The integration of nanoporous materials such as metal organic frameworks (MOFs) with sensitive transducers can result in robust sensing platforms for monitoring gases and chemical vapors for a range of applications. Here, we report on an integration of the zeolitic imidazolate framework – 8 (ZIF-8) MOF with surface acoustic wave (SAW) and thickness shear mode quartz crystal microbalance (QCM) devices to monitor carbon dioxide (CO2 ) and methane (CH4 ) under ambient conditions. The MOF was directly coated on the Y-Z LiNbO3 SAW delay lines (operating frequency, f 0 = 436 MHz) and AT-cut quartz TSM resonators (resonant frequency, f 0 = 9 MHz) and the devices were tested for various gases in N2 under ambient conditions. The devices were able to detect the changes in CO2 or CH4 concentrations with relatively higher sensitivity to CO2, which was due to its higher adsorption potential and heavier molecular weight. The sensors showed full reversibility and repeatability which were attributed to the physisorption of the gases into the MOF and high stability of the devices. Both types of sensors showed linear responses relative to changes in the binary gas compositions thereby allowing to construct calibration curves which correlated well with the expected mass changes in the sorbent layer based on mixed-gas gravimetric adsorption isotherms measured on bulk samples. For 200 nm thick films, the SAW sensitivities to CO2 and CH4 were 1.44 × 10 −6 /vol% and 8 × 10 −8 /vol%, respectively, against the QCM sensitivities 0.24 × 10 −6 /vol% and 1 × 10 −8 /vol%, respectively, which were evaluated as the fractional change in the signal. The SAW sensors were also evaluated for 100 nm–300 nm thick films, the sensitivities of which were found to increase with the thickness due to the increased number of pores for the adsorption of a larger amount of gases. In addition, the MOF-coated SAW delay lines had a good response in wireless mode, demonstrating their potential to operate remotely for the detection of the gases at emission sites across the energy infrastructure.